NATURE OF COMPETITION IN THE AUDITING PROFESSION IN NIGERIA: THE PUBLIC ACCOUNTANT’S VIEW - Ibeaja, Uzoma (EBSU Journal of Social Sciences and Humanities, 2022)
An audit involves searching and verifying the accounting records and examining other evidence supporting the financial statements. By obtaining an understanding of the company’s internal control, inspecting documents, observing assets, making inquiries within and outside the company, and performing other auditing procedures, the auditor will gather the evidence necessary to issue an audit report. The provision of services other than audit is a potential area of risk to objectivity on the part of the auditor identified in the statement on integrity, objectivity and independence. This paper looks at the nature of competition in the auditing profession and examines the elements of audit risk and factors that may increase or decrease audit quality in line with the performance of non-audit services by auditors. It was suggested, among others, that rotation of external auditors in all sectors should be encouraged to avoid cover up in their reporting.